OPERATIONS THROUGHPUT AS A DETERMINANT OF GOLDEN-HOUR IN MASS-GATHERING MEDICINE - Khan, I. D.; Asima, B.; Khan, Sh. A. (International Journal of Medicine and Medical Research, 2017)
BACKGROUND Golden-hour, a time-tested concept for trauma-care, involves a systems approach encompassing healthcare, logistics, geographical, environmental and temporal variables. Golden-hour paradigm in mass-gathering-medicine such as the Hajj-pilgrimage entwines along healthcare availability, accessibility, efficiency and interoperability; expanding from the patient-centric to public-health centric approach. The realm of mass-gathering-medicine invokes an opportunity for incorporating operations-throughput as a determinant of golden-hour for overall capacity-building and interoperability. METHODS Golden-hour was evaluated during the Indian-Medical-Mission operations for Hajj-2016; which established, operated and coordinated a strategic network of round-the-clock medical operations. Throughput was evaluated as deliverables/time, against established Standard-Operating-Procedures for various clinical, investigation, drug-dispensing and patient-transfer algorithms. Patient encounter-time, waiting-time, turnaround-time were assessed throughout echeloned healthcare under a patient-centric healthcare-delivery model. Dynamic evaluation was carried out to cater for variation and heterogeneity. RESULTS Massive surge of 3,94,013 patients comprising 2,25,103 males (57.1%) and 1,68,910 females (42.9%) overwhelmed the throughput capacities of outpatient attendance, pharmacy, laboratory, imaging, ambulance, referrals and documentation. There was delay in attendance, suspicion, diagnosis and isolation of patients with communicable infections. The situational-analysis of operations-throughput highlights wasted turnaround-time due to mobilization of medical-team, diverting critical healthcare resources away from emergency situations. CONCLUSION Time being a crucial factor in the complexity of medical-care, operations-throughput remains an important determinant towards interoperability of bottlenecks, thereby being a determinant of golden-hour in mass-gathering-medicine. Early transportation of patient to definitive-care reduces treatment initiation-time, notwithstanding logistics of communication, evacuation, terrain and weather being deterministic in outcome. Golden-hour needs to be emphasized under a population-based approach targeting the clientele towards administering first-aid and reaching out to hospital within the golden-hour.